Urban competitiveness vis-a-vis sustainable urban development: A discourse on urban development in Malaysia - Fatimah Yusof; Katiman Rostam; Zikri Muhammad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
With the advent of economic globalization, sustainable urban development efforts are facing a new challenge whereby cities must not only be seen as sustainable and livable but also competitive enough in attracting foreign direct investments. As such, local authorities now find themselves struggling to achieve sustainable urban development objectives while at the same time under great pressure to create favourable climates for economic investment particularly in the manufacturing and service sectors. The two sustainability and competitiveness concepts may not be entirely compatible but they are organically interrelated. This article discusses both concepts, highlights their differences and similarities, and addresses some of the common elements which could be applied in the field of urban management. The paper concludes that although the relationships between urban sustainability and urban competitiveness are not entirely adversarial, fundamental incongruities in objectives and impacts remain. These have the potentials of generating conflicts in the course of urban management not least because they were motivated by different values. What is needed then is a more pragmatic approach that could reconcile the divergent objectives, a challenge that only amplifies the importance of the synthesising role of local authorities